STRUCTURAL GEOLOGY AND TECTONICS (Journal of Universal Science Research, 2024)
Structural geology and tectonics are fundamental disciplines within the field of geology, providing vital insights into the deformation and displacement processes that shape the Earth's crust. This abstract explores the fundamental principles and methodologies employed in studying the structures and tectonic processes that occur within the Earth's lithosphere. It discusses the classification and characteristics of geological structures, including folds, faults, and fractures, and emphasizes their significance in deciphering the tectonic history of a region.